Microbiome-Inspired Green Infrastructure: A Toolkit for Multidisciplinary Landscape Design. Issue 12 (December 2020) - Watkins, Harry; Robinson, Jake M.; Breed, Martin F.; Parker, Brenda; Weinstein, Philip
Abstract : Incorporating recent advances in environmental microbiome research and policy is a major challenge for urban design. We set out a framework for managing construction projects so that multidisciplinary teams of researchers and practitioners can explicitly consider environmental microbiota in design and construction contexts, thereby increasing ecosystem functionality and public health.